Rancang Bangun Sistem Rekrutmen dan Seleksi Tenaga Kontrak Dinas Pendidikan Kota Surabaya Menggunakan Administrative Workflow System - Rizky, Fikry Nurris; Tjandrarini, A.B.; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Dinas Pendidikan (dispendik) Surabaya is an institution responsible for the academic in the city surabaya. In the recruitment and selection dispendik surabaya still use form paper and physical documents, sparking four problems found, namely: needs save document, the lost documents, delay selection process, the entry applicants and information about the assignment need a long time. Based on the problems on, found new risk, on how ensure recruitment process and selection keep going well although the paper was replaced to digital system. To complete the risk is found a theory, namely subsisting workflow system. To help Dispendik Surabaya in solving the existing, so the production recruitment system and selection staff on contract using sub sisting workflow system web based. The recruitment testing system and selection staff on contract it may help the Dispendik Ssurabaya reducing the paper documents to digital document of 71% of total at least documents for every applicants that should be kept. Based on the results of the questionnaire, this system shows 83.8% were among the interval 81% and 100% that category in a very good.Keyword: Recruitment, Selection, Contract Workers, Administrative Workflow System, web-based